2021
DOI: 10.3390/jmmp5040134
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multidirectional Wire Arc Additive Manufacturing (WAAM) Process with Pure Object Manipulation: Process Introduction and First Prototypes

Abstract: Wire Arc Additive Manufacturing (WAAM) with eccentric wire feed requires defined operating conditions due to the possibility of varying shapes of the deposited and solidified material depending on the welding torch orientation. In consequence, the produced component can contain significant errors because single bead geometrical errors are cumulatively added to the next layer during a building process. In order to minimise such inaccuracies caused by torch manipulation, this article illustrates the concept and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Uncontrolled heat impact can not only result in a deterioration of the quality of the produced part but may also lead to its complete destruction. To achieve proper temperature control, it is possible to use preliminary simulations and optimize the robotic arm's motion trajectory during the additive manufacturing process [16]. Computer computational programs for modeling the thermal regime of printing using arc welding can employ heat propagation equations based on the Goldak model.…”
Section: Methodsmentioning
confidence: 99%
“…Uncontrolled heat impact can not only result in a deterioration of the quality of the produced part but may also lead to its complete destruction. To achieve proper temperature control, it is possible to use preliminary simulations and optimize the robotic arm's motion trajectory during the additive manufacturing process [16]. Computer computational programs for modeling the thermal regime of printing using arc welding can employ heat propagation equations based on the Goldak model.…”
Section: Methodsmentioning
confidence: 99%
“…To build these structures with planar slicing, robotic cells integrate additional positioning axes for rotating the workpiece to custom orientations. Additional planar layers are then printed in the 1G welding position [11] as shown in Figure 2. One limitation of this approach is the constraint of the build area that comes with the additional positioning axes, as the workpiece is reoriented between printed sections.…”
Section: State Of the Artmentioning
confidence: 99%
“…The experimental results showed that surface roughness has a significant effect on the signal-to-noise ratio (SNR) of internal through-hole detection, and surface waviness has a significant effect on the sensitivity of superficial crack detection. In one study, Parmar et al [123] stated that the single-bead geometrical errors produced during the building process of the next layer of material in WAAM can be minimised by incorporating robotic and welding technologies. Xia et al [124] investigated the anomalies generated during the deposition process, such as humping, spattering, and robot suspending.…”
Section: Crackingmentioning
confidence: 99%
“…In one study, Parmar et al. [123] stated that the single-bead geometrical errors produced during the building process of the next layer of material in WAAM can be minimised by incorporating robotic and welding technologies. Xia et al.…”
Section: Challenges Facing the Application Of Waam In Aerospace And A...mentioning
confidence: 99%